Welfare effects of natural resource privatization: a dynamic analysis. (5th June 2020) - Okonkwo, Jennifer U.; Quaas, Martin F.
Abstract: This paper sets up a dynamic model to study the distributive effects of privatizing an open access resource. We show that with or without discounting, privatization is not always Pareto improving. We further derive conditions under which the poor are made worse off when private use rights are equally distributed compared to a situation with open access resource. These conditions imply that privatization is Pareto improving if the natural resource is sufficiently productive, inequality in alternative private project opportunities is low, and if there is no discounting. In addition, we show that once reduction in income from resource harvesting during the transition to a new steady state is accounted for, privatization is desirable for the poor only for very productive natural resources and low discount rates.